Wealth and poverty - Gilder, George F. (New York : Basic Books, 1981)
In 'Wealth and Poverty' Gilder extended the sociological and anthropological analysis of his early books in which he had advocated for the socialization of men into service to women through work and marriage. He wove these sociological themes into the economic policy prescriptions of supply-side economics. The breakup of the nuclear family and the policies of demand-side economics led to poverty. Family and supply-side policies led to wealth.
Includes index.
Includes bibliographical references: p. 289-295.
rpm 21/06/2017
Loans
Keywords: Capitalism; Wealth; Poverty; Supply-side economics; United States $1 (BEconomic conditions $1 (B1945-s; United States $1 (BEconomic policy.s; United States